Representation of the Nazi Crimes in Donbass in Soviet Documentary and Fictional Cinema (1943–1950) - Tytarenko, Olena (Faces of War, 2025)
Soviet documentary and fiction cinema of World War II and the first postwar years created several images related to Donbas. This region had played a significant role in Soviet socio-political discourse since prewar times. The article focuses on the peculiarities of the representation of Nazi crimes in Donbas. The author analyses the main fiction and documentary films that feature episodes of crimes committed during the German occupation, describes their historical context, and characterises the degree of influence these scenes had on the population. It is noted that the subject of Nazi crimes in Donbas first appears in the visual images of the destruction of industrial and social infrastructure caused by the Nazis. The issue of the murder of the population of the occupied territories is explored in documentaries related to the central site of mass crimes — the 4–4 bis mine in Stalino (today Donetsk). Fiction cinema dedicated to the topic of the wartime Donbas is represented by the films The Unconquered (Nepokorennyye), It Happened in Donbas (Eto bylo v Donbasse), The Young Guard (Molodaya gvardiya), and A Great Life (Bol’shaya zhizn’). The key focus is on the issues of the struggle against Nazism and post-war reconstruction. The films show the torture and murder of members of the anti-Nazi Resistance movement, including juveniles, the executions of Soviet prisoners of war, the deportation of civilians to Germany, and, for the first time in Soviet cinema, a scene of a mass execution of the Jewish population. Despite several historical inconsistencies, as the films were usually based on literary works, these films were very popular among the population that survived the occupation. Both abstract and concrete images of victims of the Nazi regime evoked allusions to their suffering caused by the war and occupation. The images of the wartime Donbas are still an important source for the perspective of reflecting the historical processes of the past and for studying the system of influence on the outlook and value coordinates of the population in different historical epochs.